PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN PADA SMP NEGERI 134 JAKARTA - Muhammad Ainur Rony (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2011)
The library is a tool that is on an organization to educate members of the organization. A good library should ideally have a number of books a lot and has a number of active members whose numbers too much. Compensation obtained from the library of the large number of books is the difficulty of administering the library. So as to facilitate the administrative process library that has the number of lots, it would require an information system intended to assist the process of library administration and can provide useful information for library management. In addition to improving the administration process and provide information, library information systems can also improve service to its members. The design of the library information system using the waterfall method using VB-based application. Net. This system will use a one-tier model where applications and databases are on one computer. The method used in this design by using observation, interviews and analysis of related documents.Keywords : Library, waterfall, VB. Net, Information System, Database